An Agent-Based Approach for Constructing Software Systems of Virtual Simulation - Hongbing, Li; Bo, Meng; Shifu, Chen (International Journal of Virtual Reality, 2000)
The design and construction of virtual reality environments involve technologies such as computer graphics, image processing, pattern recognition, intelligent interface, artificial intelligence, voice recognition, network, parallel processing, and high-performance computing. Some researchers insist that object-oriented and agent-oriented technologies are fundamental for virtual reality system design. This paper applies artificial intelligence to the design of virtual reality systems. Agents are constructed by using object-oriented methods and a set of underlying computing models, such as neural networks, genetic algorithms, expert systems, and plan managers. Some object-oriented frameworks of these computing models are presented to illustrate this approach. The example of a spaceship game will illustrate interactions among environments, agents, and underlying computing models. The approach and reusable class library presented herein can be applied to various virtual reality environment simulations and intelligent applications.